Transcriptomic analysis of the venom gland and enzymatic characterization of the venom of phoneutria depilata (Ctenidae) from Colombia (2022)
ABSTRACT: The transcriptome of the venom glands of the Phoneutria depilata spider was analyzed using RNA-seq with an Illumina protocol, which yielded 86,424 assembled transcripts. A total of 682 transcripts were identified as potentially coding for venom components. Most of the transcripts found were neurotoxins (156) that commonly act on sodium and calcium channels. Nevertheless, transcripts coding for some enzymes (239), growth factors (48), clotting factors (6), and a diuretic hormone (1) were found, which have not been described in this spider genus. Furthermore, an enzymatic characterization of the venom of P. depilata was performed, and the proteomic analysis showed a correlation between active protein bands and protein sequences found in the transcriptome. The transcriptomic analysis of P. depilata venom glands show a deeper description of its protein components, allowing the identification of novel molecules that could lead to the treatment of human diseases, or could be models for developing bioinsecticides. The transcriptome of the venom glands of the Phoneutria depilata spider was analyzed using RNA-seq with an Illumina protocol, which yielded 86,424 assembled transcripts. A total of 682 transcripts were identified as potentially coding for venom components. Most of the transcripts found were neurotoxins (156) that commonly act on sodium and calcium channels. Nevertheless, transcripts coding for some enzymes (239), growth factors (48), clotting factors (6), and a diuretic hormone (1) were found, which have not been described in this spider genus. Furthermore, an enzymatic characterization of the venom of P. depilata was performed, and the proteomic analysis showed a correlation between active protein bands and protein sequences found in the transcriptome. The transcriptomic analysis of P. depilata venom glands show a deeper description of its protein components, allowing the identification of novel molecules that could lead to the treatment of human diseases, or could be models for developing bioinsecticides.